Showing Equivalence using Set Properties 1
In this class, We discuss Showing Equivalence using Set Properties 1.
The reader should have prior knowledge of set theory basics. Click Here
Example 1:
A – (B–C) = (A – B) ∪ (A∩C)
Solution:
A -(B–C)
A – (B ∩ C’)
A ∩(B ∩ C’)’
A ∩ (B’ ∪ C) from de Morgan law
(A ∩ B’) ∪ (A∩C) from distributive law
(A – B) ∪ (A ∩ C)
Example 2:
If A ∪ B = A ∪ C and A ∩ B = A ∩ C then show that B = C
Solution:
Take A ∪ B = A ∪ C
B ∩ (A ∪ B) = B ∩(A ∪ C)
Take LHS B ∩ (A ∪ B)
= B since B ⊆ A ∪ B
Take RHS B ∩(A ∪ C)
(B ∩ A) ∪ ( B ∩ C) from distributive law
(A ∩ B) ∪ ( B ∩ C) from commutative law
(A ∩ C) ∪ ( B ∩ C)
(A ∪ B) ∩ C
(A ∪ C) ∩ C
= C since C ⊆ A ∪ C